2020
DOI: 10.1007/s43440-020-00152-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatments of COVID-19

Abstract: The viral infection due to the new coronavirus or coronavirus disease 2019 (COVID-19), which was reported for the first time in December 2019, was named by the World Health Organization (WHO) as Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV2), because of the very similar genome and also its related symptoms to SARS-CoV1. The ongoing COVID-19 pandemic with significant mortality, morbidity, and socioeconomic impact is considered by the WHO as a global public health emergency. Since there is no specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 254 publications
(338 reference statements)
0
39
0
12
Order By: Relevance
“…Nowadays the coronavirus COVID-19 pandemic is a global dilemma. Since the main pathogenic mechanism of the disease is unclear, many drugs have been evaluated in an attempt to relieve the symptoms (27). One of the suggestive agents used for systemic treatment of COVID-19 is levamisole because of its wide variety of immunological effects including regulation of neutrophils, macrophages, and T-cell activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays the coronavirus COVID-19 pandemic is a global dilemma. Since the main pathogenic mechanism of the disease is unclear, many drugs have been evaluated in an attempt to relieve the symptoms (27). One of the suggestive agents used for systemic treatment of COVID-19 is levamisole because of its wide variety of immunological effects including regulation of neutrophils, macrophages, and T-cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigation found that lmmunomodulators play an important role in management of patients infected with COVID-19 (27,29). Levamisole is a safe and successful immunomodulatory drug, suggesting that in COVID-19 patients, levamisole may also contribute to attenuating the immune response..…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there are some antiviral medications capable of curbing viral replication, viral assembly and systemic spread of infection in the body, as well as some anti-inflammatory treatments capable of suppressing the post-infectious hyperinflammation, which have been trialed on COVID-19 patients ( Fig 1 ). Although many trials supported the efficacy of these treatments for COVID-19 patients [10] , [11] , [12] , [13] , [14] , [15] , especially in terms of decrease in hospitalization, improvement of hospitalized patients’ condition, and reduced risk of ICU admission and mortality; further evidence failed to prove significant clinical benefit in use of some of the mentioned treatments (e.g. remdesivir and IL-6 receptor antagonists) [8] , [16] , and so regional guidelines for COVID-19 management have remained to be largely varied [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%
“…As of Feb 2021, the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) [1][2] has infected more than 100 million people and cause two million life. Although several drugs have been "repurposed" for the treatment of SARS-CoV-2 infection, [3][4] there is still a pressing need to identify novel anti-SARS-CoV-2 therapeutics.…”
Section: Introductionmentioning
confidence: 99%